Aplikasi Mobile Untuk Menekan Biaya Penjualan Produk Pertanian Lokal - Tjong, Wan Sen (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Research aim: This mobile application development aims to directly connect local agricultural producers to their buyers without any intermediary party in order to keep the selling costs minimum. Design/Methode/Approach: Rapid Application Development method with User Oriented are used in this research, which allows a relatively short development time and supports a more intense interaction with the related stakeholders. Research Finding: This research finds that simplification of transactions and more exposure through this application is very important. Theoretical contribution/Originality: This application has unique functions and interfaces that are designed as simple as possible to be easily operated by local agricultural producers, even with minimum digital literacy level. Practitionel/Policy implication: This implicated on application speed factor, data transmission size, and minimum hardware requirements are also the main criterias on which this application development is based. The result is a new and unique mobile application which is easy to use, does not consume too much internet quota, and supports older smartphones which are very beneficial for stakeholder. Research limitation: However system limitations such as integration with digital payment, rating systems, and recommendation systems still not covered yet.